Two new species of oribatid mites (Acari, Oribatida) from the Afrotropical region - Sergey G. Ermilov; Stefan Friedrich; Dilian Georgiev (Persian Journal of Acarology)
We describe two new species of oribatid mites (Oribatida) based on adult males—Gymnobodes schedeli sp. nov. (Carabodidae) collected from rotten wood and humus under a tree in Zambia and Galumna (Galumna) luisi sp. nov. (Galumnidae) collected from detritus among Cyperus papyrus in Uganda. Gymnobodes schedeli sp. nov. differs from all species of the genus by the presence of a depression in the basal part of the prodorsum, and by the notogastral ornamentation/sculpturing. Galumna (Galumna) luisi sp. nov. differs from G. (G.) incisa by the body size, the morphology of the rostrum and notogastral porose areas Aa and A3, the presence of a rostral bulge and a long longitudinal fold having short lateral branches in the anteromedial part of the notogaster, the absence of a median pore, and the location of the notogastral lyrifissure im and leg famulus.